2020
DOI: 10.1111/sms.13674
|View full text |Cite
|
Sign up to set email alerts
|

Does an effective shoulder injury prevention program affect risk factors in handball? A randomized controlled study

Abstract: Background Shoulder problems are common in handball, but injury risk reduction is possible by implementing a prevention program. However, player compliance to the program remains a challenge, with feedback from players that the program is too time consuming. Aim To develop a more efficient program, we aimed to assess the effect of the Oslo Sports Trauma Research Center shoulder injury prevention program on external rotation (ER) strength and internal rotation (IR) range of motion (ROM), considered to represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
(64 reference statements)
1
19
0
4
Order By: Relevance
“…Despite the multiple beneficial effects derived from handball practice, such as improvements in cardiovascular, metabolic, muscular and psychosocial health [4][5][6], this team sport presents a high injury risk [7], mainly due to its high-intensity specific demands (i.e., rapid changes of direction, jumps with abrupt landings and repetitive throws, as well as frequent physical contact among players [8,9]). Likewise, low physical fitness, incorrect technique, lack of flexibility, and also inadequate rehabilitation treatment of injuries have been reported as risk factors related to the occurrence of injuries [10,11]. Additionally, the high training volumes and intensities that youth players undertake to achieve sporting excellence seem to contribute to the increase of the injury incidence [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the multiple beneficial effects derived from handball practice, such as improvements in cardiovascular, metabolic, muscular and psychosocial health [4][5][6], this team sport presents a high injury risk [7], mainly due to its high-intensity specific demands (i.e., rapid changes of direction, jumps with abrupt landings and repetitive throws, as well as frequent physical contact among players [8,9]). Likewise, low physical fitness, incorrect technique, lack of flexibility, and also inadequate rehabilitation treatment of injuries have been reported as risk factors related to the occurrence of injuries [10,11]. Additionally, the high training volumes and intensities that youth players undertake to achieve sporting excellence seem to contribute to the increase of the injury incidence [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies in the literature which investigate the effects of training programs on the range of motion in different sports disciplines. Fredriksen and Myklebust investigated the effect of the OSTRC Shoulder Injury Prevention Program on handball players' range of motion and stated that it had no effect on IR, ER and the total range of motion [8]. Oranchuk et al also investigated the effect of an eight-week sports-specific training program with resistance bands and general training program on the glenohumeral range of motion in softball players, and at the end of the study, they found that both training programs did not cause a statistically significant difference on the ER and IR range of motion [18].…”
Section: Resultsmentioning
confidence: 99%
“…The Oslo Sports Trauma Research Center (OSTRC) shoulder injury prevention program is an exercise program developed to increase IR range of motion, external rotator muscle strength and scapular muscle strength and to improve kinetic chain involvement and thoracic mobility [7,8]. In a randomized controlled trial of 660 elite handball players, the OSTRC Shoulder Injury Prevention program was applied three times a week as a part of the handball warmup.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the handheld dynamometer (HHD) used for isometric strength measurements is low-cost, portable, and suitable for eld use. Additionally, the HHD has also demonstrated high intra-and inter-rater reliability for isometric shoulder strength measurements, making it a suitable alternative to an isokinetic device [51,52]. Furthermore, using HHD for strength measurements may also lead to a greater protocol consistency across studies thus enabling researchers to draw valid conclusions while comparing the studies.…”
Section: Strength Intervention-based Performance Outcome Measuresmentioning
confidence: 99%